2015
DOI: 10.1021/acs.nanolett.5b02099
|View full text |Cite
|
Sign up to set email alerts
|

Dimensionality of Rolled-up Nanomembranes Controls Neural Stem Cell Migration Mechanism

Abstract: We employ glass microtube structures fabricated by rolled-up nanotechnology to infer the influence of scaffold dimensionality and cell confinement on neural stem cell (NSC) migration. Thereby, we observe a pronounced morphology change that marks a reversible mesenchymal to amoeboid migration mode transition. Space restrictions preset by the diameter of nanomembrane topography modify the cell shape toward characteristics found in living tissue. We demonstrate the importance of substrate dimensionality for the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 67 publications
3
42
0
Order By: Relevance
“…For neuron cells, the microtubular geometry can even guide the growth direction of the axon (panel (ii) of Figure c), and the cells growing inside the microtubes demonstrated increased photoresistance . Recently, Schmidt and co‐workers investigated the interactions between rolled‐up microtube with different mammalian cells, and their influences on cellular events were investigated in detail . It is expected that these 3D structures can be used to gain molecular insights into key cellular events occurring in 3D microenvironments.…”
Section: Biomimetic Nanomembranesmentioning
confidence: 99%
“…For neuron cells, the microtubular geometry can even guide the growth direction of the axon (panel (ii) of Figure c), and the cells growing inside the microtubes demonstrated increased photoresistance . Recently, Schmidt and co‐workers investigated the interactions between rolled‐up microtube with different mammalian cells, and their influences on cellular events were investigated in detail . It is expected that these 3D structures can be used to gain molecular insights into key cellular events occurring in 3D microenvironments.…”
Section: Biomimetic Nanomembranesmentioning
confidence: 99%
“…In recent years, consid erable research has been put into this field, and advanced devices with improved capaci tance density and energy density have been developed. [28,[41][42][43]142,143] Applying the selfrolling technique, scalable onchip EES microdevices can be designed when combining with wellestablished semicon ductor planar processing technologies. [140] Qu et al designed a fibershaped supercapacitor with high energy densities and long life stability based on hollow graphene/conducting polymer fiber electrodes.…”
Section: Rolled-up Nanotechnology For Ultracompact On-chip Ees Microdmentioning
confidence: 99%
“…However, previous understanding of cell behaviors, including cell migration, directed mitosis, and differential growth is mainly based on studies of cells cultured on flat, 2D commercial culture substrates . In recent years, the results of cell behavior studies in 3D culture scaffolds have revealed several differences from that in 2D substrates, such as neurite outgrowth, neural stem cell migration, and tumor cell division . Therefore, biocompatible 3D culture scaffolds which can more closely mimic the natural complex 3D microenvironment in vivo are urgently needed.…”
Section: Introductionmentioning
confidence: 99%
“…Microtubes, which have very high aspect ratio with variable diameter in nano‐ and micrometer scale, have almost universal applications in areas as diverse as microoptics, resonators, microrobots, microscale energy storage, micromedical devices, and microbiology . Especially in the field of microbiology, microtube array has great potential as a powerful tool to research the biological mechanisms in 3D culture environment because of the dissimilarity between 2D flat surfaces and 3D extracellular environments in which cells routinely operate in vivo .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation